PENGARUH ICAP MODEL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS - Nuraini Sri Bina; Rahmi Ramadhani; Siti Fatimah Sihotang; Ramadhan Nasution (Journal of Authentic Research on Mathematics Education (JARME), 2022)
The learning model is one aspect that can improve the cognitive abilities of students when applied properly by educators. One of the new learning models and based on previous research that is effectively applied in learning is the ICAP Model. The purpose of this study was to see whether there was a positive effect of the application of the ICAP learning model on students' mathematical communication skills. The paradigm used in this research is Postpositivism, with an experimental method. Data collection techniques through research instruments in the form of mathematical communication skills tests that have been tested beforehand to see the validity and reliability. The data analysis technique used regression test through the SPSS application. The results obtained through data processing using SPSS is that there is a positive effect of the application of the ICAP learning model on students' mathematical communication skills in the Statistics course.